Joule heating-induced sp2-restoration in graphene fibers. (February 2019) - Noh, Sung Hyun; Eom, Wonsik; Lee, Won Jun; Park, Hun; Ambade, Swapnil B.; Kim, Sang Ouk; Han, Tae Hee
Abstract: Joule heating can instantaneously achieve high temperatures (>2000 °C) by applying electrical current on a resistive material. This ohmic heating by the passage of an electric current through a conducting domain may effectively heal the defective sites (i.e., vacancies, structural defects, and sp 3 oxygen groups) of graphene oxide (GO) and revert them into sp 2 domains. Indeed, the direction of electric field controls the texture of GO with preferential alignment, which significantly affects the transport properties along the fiber axis. Here we present electrical current-induced manipulation of resistive domain (i.e. Joule heating) as an effective healing method for the defect sites in GO fibers (GOFs). Systematic control of input current restores the sp 2 lattice structures within fibers in a well-controlled manner. Structural evolution mechanism is proposed for multilayer stacked graphitic structures as well as graphene sheet plane under the reduction process. This defect-healing principle is rapid, environmentally benign and energy efficient, compared to other defect restoration methods, and yields tailored-aligned fibers with a high current-carrying capability and facile charge transport, which is potentially beneficial for power cables and other relevant applications. Graphical abstract: Current-induced self-annealing on graphene fibers for the healing of defects in graphene fibers. Image 1